B-site order/disorder in A2BB′O6 and its correlation with their magnetic property - Alam M.; Chatterjee S. (My University, 2025)
The disorder in any system affects their physical behavior. In this scenario, we report the possibility of disorder in A2BB′O6 oxides and their effect on different magnetic properties. These systems show anti-site disorder by interchanging B and B′ elements from their ordered position and giving rise to an anti-phase boundary. The presence of disorder leads to a reduction in saturation M and magnetic transition temperature. The disorder prevents the system from sharp magnetic transition which originates short-range clustered phase (or Griffiths phase) in the paramagnetic region just above the long-range magnetic transition temperature. Further, we report that the presence of anti-site disorder and anti-phase boundary in A2BB′O6 oxides give different interesting magnetic phases like metamagnetic transition, spin-glass, exchange bias, magnetocaloric effect, magnetodielectric, magnetoresistance, spin-phonon coupling, etc. © 2023 IOP Publishing Ltd.